Comparison of growth characteristics of in vitro cultured granulosa cells from geese follicles at different developmental stages - Deng, Yan. (Biosci Rep, 2018)
Granulosa cells (GCs) are essential components of follicles and are involved in regulating the process of follicles development. However, comparative studies on GCs isolated from different staged follicles have not been conducted in goose. The aim of the present study was to identify the growth characteristics of goose GCs from pre-hierarchical (6–10 mm) and hierarchical (F4–F2, F1) follicles. Our results showed that the three cohorts of cells had different tolerance to collagenase and had noticeable morphological differences. The F1 granulosa layers were fully digested by 0.1% collagenase, while higher concentration (0.3%) was used for both F4–F2 and pre-hierarchical granulosa layers. In the state of suspension, the diameter of F1 individual cell was larger than the other two cohorts. However, after adhering to the culture plate, cells of F1 just had changes in the diameter accompanied by small bright spots, while both pre-hierarchical and F4–F2 GCs proliferated rapidly with spreading and irregularly shaped voids. Furthermore, all attached cells could be stained by the follicle-stimulating hormone receptor antibody. Analyses of both growth curve and the mRNA expression profiles of genes related to cellular proliferation, apoptosis, and steroidogenesis suggested that three cohorts of in vitro cultured GCs had different physiological viability and functions. Taken together, the present study not only revealed differences of the growth characteristics among three cohorts of goose GCs from pre-hierarchical, F4–F2 and F1 follicles, but also optimized the in vitro culture system of geese different staged GCs.